2020
DOI: 10.2147/hiv.s242166
|View full text |Cite
|
Sign up to set email alerts
|

<p>Level of Knowledge About Prevention of Mother-to-Child Transmission of HIV Option B+ and Associated Factors Among ANC Clients in Kombolcha Town, South Wollo Amhara Regional State, Ethiopia, 2017</p>

Abstract: The purpose of this study was to assess the level of knowledge about prevention of mother-to-child transmission option B+ and associated factors among antenatal care clients in Kombolcha town; 2017. Methods: An institutional-based cross-sectional study design was conducted from May 1 to 30, 2017. Simple random sampling techniques were used to select 129 study subjects from May 1 to 30, 2017. A chi-square test was done by using SPSS 20 to assess the association between the dependent and independent variables. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Parity was associated with knowledge about MTCT of HIV/AIDS and its prevention. Consistent with other studies [ 27 , 29 ], in this study, multiparous women had higher odds of knowledge about MTCT of HIV/AIDS and its prevention. This may be because multiparous women may have a greater likelihood of exposure to maternal health services, including HIV testing and counseling services, during their consecutive pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Parity was associated with knowledge about MTCT of HIV/AIDS and its prevention. Consistent with other studies [ 27 , 29 ], in this study, multiparous women had higher odds of knowledge about MTCT of HIV/AIDS and its prevention. This may be because multiparous women may have a greater likelihood of exposure to maternal health services, including HIV testing and counseling services, during their consecutive pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Maternal knowledge about MTCT of HIV/AIDS and its prevention is a cornerstone for elimination of MTCT of HIV. Although the majority of the population in SSA are lived in rural areas with restricted availability and accessibility of health facilities, most of the studies on knowledge about MTCT of HIV/AIDS and its prevention were conducted among available women, such as those who came to the health facility for their antenatal care follow up [20][21][22][23][24]. In addition, up to our knowledge, there is no updated information on this regard using nationally representative data (using the recent DHS surveys) at the SSA scale.…”
Section: Introductionmentioning
confidence: 99%
“…The 2016 EDHS report showed that urban women are more likely than rural women to receive any ANC from a skilled provider; 90% of urban women received any ANC service from a skilled provider as compared to 58% rural women [ 33 ]. The study done in Amhara regional state, Ethiopia showed that ANC service utilization has positive significant association with knowledge of the mother-to-child transmission of HIV [ 40 ]. The current study and the previous study done in Ethiopia [ 28 ] showed that exposure to mass media has a positive and significant association with MTCT of HIV-related knowledge of reproductive-age women.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to a study in Ethiopia which found 61% of mothers had good knowledge using a similar cut off (although with fewer questions). 26 Studies from Malawi, Ghana, Uganda and elsewhere in Tanzania have reported lower levels of knowledge (25–35%). This discrepancy could likely be due to the spread of PMTCT messages with time, perhaps more than the differences in assessment methods.…”
Section: Discussionmentioning
confidence: 99%